HIGHER EDUCATION IN COMMUNITY EMPOWERMENT BASED ON THE STRENGTH OF TECHNOLOGY AND INFORMATION, ONLINE MARKETING SYSTEM APPROACH - Marselinus Wishnu Wardhana, (International Journal of Social Science, 2022)
The chain problem that really stuck up during the Corona 19 pandemic was the limited knowledge/skills and techniques that could be accessed in terms of technology. This aspect is still a fundamental problem for community groups regarding product development technology. Fundamental changes through innovation will bring new markets. These developments eventually create differentiated products and services. This research places Higher Education in community empowerment as an object of basic study in carrying out steps to empower rural communities, with the aim of reviving the community's economy based on the power of technology and information, namely through an online marketing system. This research uses a qualitative descriptive approach with a study of online seller communities that have the concept of empowerment. Methods of data collection through observation, interviews, and documentation as well as the participation of the author, using the data triangulation analysis method, namely grouping the data that has been obtained, then reduced, drawn conclusions, presented with a description systematically so that it can comprehensively describe the steps of empowerment. In this study, it was found that the strategy of Higher Education in community empowerment is through the stages of socialization, the introduction of tools, operations, and segmentation analysis. Economic impacts can be identified through members' contributions to operational empowerment. With this, the concept of collaborative synergies through the dropship system is a new strategy in empowerment, because it can be done from any angle, and can be integrated into various other media marketplaces